2013
DOI: 10.1002/ptr.5084
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy of Benign Prostatic Hyperplasia. A Minireview

Abstract: Benign prostate hyperplasia (BPH) is a common condition affecting older men, with an incidence that is age-dependent. Histological BPH, which typically develops after the age of 40 years, ranges in prevalence from >50% at 60 years to as high as 90% by 85 years of age. Typical symptoms include increased frequency of urination, nocturia, urgency, hesitancy, and weak urine stream. Conventional medicines used for the treatment of BPH include alpha blockers and 5-alpha reductase inhibitors. This articles review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 52 publications
2
63
0
11
Order By: Relevance
“…However, they may cause adverse effects such as loss or reduced libido, erectile dysfunction, orgasmic, ejaculatory dysfunction, development of high‐grade prostate cancers, potential negative cardiovascular events, and depression (Edwards, ). As a substitute, phytotherapeutics have been playing an important role in the treatment of BPH for over decades as they are well tolerated by most users and are not associated, contrarily to conventional medicine, with serious adverse events, including herb–drug interactions (Pagano et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, they may cause adverse effects such as loss or reduced libido, erectile dysfunction, orgasmic, ejaculatory dysfunction, development of high‐grade prostate cancers, potential negative cardiovascular events, and depression (Edwards, ). As a substitute, phytotherapeutics have been playing an important role in the treatment of BPH for over decades as they are well tolerated by most users and are not associated, contrarily to conventional medicine, with serious adverse events, including herb–drug interactions (Pagano et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study confirmed the potential role of β-sitosterol to manage BPH in human and animal models. Pagano et al [47] reported that β-sitosterol could improve urological symptoms and urine flow rate in BHP men. The relaxant effect of phytosterols from flaxseed, fruits of saw palmetto, and red clover on isolated prostate strips have been demonstrated [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…) (Ho et al , ; Rosner, 2012; Elamin and Montori, 2012; Varoni et al , 2014). For this reason, although traditional, narrative review articles on the efficacy and the safety of herbal medicine continue to be published (for example, Bella and Shamloul, ;Gulati, ; Pagano et al , ; Stohs, ; Stohs, ; Chingwaru et al , ; Gulati, ; Stohs and Hartman, ), systematic reviews increasingly are replacing them.…”
Section: The Clinical Efficacy Of Herbal Remediesmentioning
confidence: 99%